Measurement system for medical ultrasonic pulse spectroscopy - RICHTER, K. P.; LANGE, P.; MILLNER, R.; HEYNEMANN, H.; RICHTER, M. I.; PRESSLER, H.; DRESCHER, Th.; LETTERER, H. (Archives of Acoustics, 1984)
A measurement system was developed to measure the ultrasonic attenuation of biological tissues in vitro. The apparatus works in transmission and pulse echo technique. The use of broad band transducers and PVDF hydrophones ensures a high sensitivity connected with a wide bandwidth. The ultrasonic attenuation of different fixed and unfixed tissues was measured. A comparison of ultrasonic data and histopathology was made.